Grounded Theory and Philosophy of Science - Nardis, Evelina De (Richtmann Publishing, 2012)
The aim of my contribution is to examine the relationship between Grounded Theory Methods and the epistemologyconcerning with the Philosophy of science. In a grounded theory approach the theory is strictly linked to practice because the elementsthat constitute the process of knowledge are not considered as things in themselves, but as discovered from the data along all stagesof research.The Grounded Theory methodology is described as having certain specific characteristics and procedures that separate thismethodologies from the others. This article set Glaserian grounded approach in a context where the methodologies are not orthodoxin the first place.